2004
DOI: 10.1038/nn1173
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical function and anxiety: controlling attention to threat-related stimuli

Abstract: Threat-related stimuli are strong competitors for attention, particularly in anxious individuals. We used functional magnetic resonance imaging (fMRI) with healthy human volunteers to study how the processing of threat-related distractors is controlled and whether this alters as anxiety levels increase. Our work builds upon prior analyses of the cognitive control functions of lateral prefrontal cortex (lateral PFC) and anterior cingulate cortex (ACC). We found that rostral ACC was strongly activated by infrequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

64
704
8
10

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 850 publications
(786 citation statements)
references
References 28 publications
64
704
8
10
Order By: Relevance
“…According to one view, while dACC is involved in dealing with non-emotional distraction (as considerable data suggests; e.g., Bush et al 1998;Carter et al 2000), rACC is involved in dealing with emotional distracters (cf. Bishop et al, 2004;Etkin et al, 2006;Whalen et al, 1998). In contrast to this view, in the current study regions of dorsal ACC were identified by the main effects of both visibility and emotionality, though the dACC region identified by the emotional main effect was slightly more posterior than to that identified by the visibility main effect.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…According to one view, while dACC is involved in dealing with non-emotional distraction (as considerable data suggests; e.g., Bush et al 1998;Carter et al 2000), rACC is involved in dealing with emotional distracters (cf. Bishop et al, 2004;Etkin et al, 2006;Whalen et al, 1998). In contrast to this view, in the current study regions of dorsal ACC were identified by the main effects of both visibility and emotionality, though the dACC region identified by the emotional main effect was slightly more posterior than to that identified by the visibility main effect.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies investigating the response to emotional distraction have also identified the recruitment of frontal, parietal and cingulate cortex (Bishop et al, 2004;Blair et al, 2007;Etkin et al, 2006;Mitchell et al 2007;Vuilleumier, et al, 2001). However, to our knowledge, no previous work has investigated the effect of distracter visibility on target processing; though related work has shown the increased recruitment of frontal and parietal areas in response to stimuli of increased visual salience (Constantinidis, 2006;Gottlieb et al, 1998;Indovina & Macaluso, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations